Pembelajaran Piano Beginner Grade CFK 1-JC Di Sekolah Musik Indonesia Cabang Puri Anjasmoro Semarang - Al Qodriyan, Aradea Rahmad; Widjajantie, Kusrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of beginner piano learning at levels CFK 1–JC 1 in a nonformal music education context, specifically within the Private Class Program at Sekolah Musik Indonesia (SMI) Puri Anjasmoro Semarang. Beginner piano instruction in nonformal institutions often faces pedagogical challenges such as differences in students’ abilities, learning pace, motivation, and initial musical background. This research aims to describe and analyze the implementation of beginner piano learning, including syllabus application, learning materials, instructional strategies, learning media, challenges encountered by teachers, and students’ learning outcomes. The study employed a descriptive qualitative approach. Data were collected through classroom observations, semi-structured interviews with piano teachers and academic administrators, and documentation analysis, including syllabi, teaching materials, and student progress reports. Data validity was ensured through source, technique, and time triangulation. The findings indicate that beginner piano learning at SMI is implemented in a gradual and flexible manner through one-to-one instruction, allowing teachers to adapt materials, methods, and tempo to individual student needs. Learning materials are structured progressively, supported by various media such as learning handbooks, student learning guides, etude compilations, and minus one accompaniment. Instructional methods include drills, demonstrations, and supporting methods adapted to students’ characteristics. Student learning outcomes show gradual improvement in technical skills, musical understanding, and learning attitudes, as documented in periodic progress reports. The study concludes that adaptive, student-centered, and tiered piano instruction is essential for effective beginner piano learning in nonformal music education settings.